Revealing Pre-service Teachers’ Reading Skills by Utilizing CEFR in their Self-assessment - Da Silva Lemos, Raquel; Elysa Hartati (JET ADI BUANA, 2021)
An English teacher should meet the standard English skills requirement since proficiency constitutes the foundation of non-native English teachers' professional confidence. This research aims to measure the pre-service teachers’ reading skills by using CEFR level and to investigate pre-service teachers’ awareness regarding their reading skills as their preparation as future English teachers. The study involved 40 (forty) students from the English program in a private University in Yogyakarta, and used Descriptive Mixed method to collect the data. The researcher used the questionnaire for the students' self-assessment, and the EF SET test to assess their reading skill level. The result of the questionnaire obtained shows 20% of students are in level A1, 25% are in level A2, 25% are in level B1, 12% are in level B2, 10% are in level C1, 8% are in the level C2). The test result shows 17% of the students are in level A1, 25% in level A2, 25% in level B1, 20% are in level B2, 8% are in level C1, and 5% are in the level C2. Six students joined the survey, of which 3 (three) rated themselves at a reading level above the result obtained on the test, and 3 (three) others rated themselves at a level lower than the result they got on the test. The result of this research showed that pre-service teachers should improve in English language proficiency and self-assessment. This knowledge expects to be used as information to those involved in the Educational field.